Spontaneous Mutations Restore the Viability of Tick-Borne Encephalitis Virus Mutants with Large Deletions in Protein C - Kofler, Regina M. (American Society for Microbiology, 2003)
The capsid protein, C, of tick-borne encephalitis virus has recently been found to tolerate deletions up to a length of 16 amino acid residues that partially removed the central hydrophobic domain, a sequence element conserved among flaviviruses which may be crucial for virion assembly. In this study, mutants with deletion lengths of 19, 21, 27, or 30 residues, removing more or all of this hydrophobic domain, were found to yield viable virus progeny, but this was without exception accompanied by the emergence of additional mutations within protein C. These point mutations or sequence duplications were located downstream of the engineered deletion and generally increased the hydrophobicity, suggesting that they may compensate for the loss of the central hydrophobic domain. Two of the second-site mutations, together with the corresponding deletion, were introduced into a wild-type genetic backbone, and the analysis of these “double mutants” provided direct evidence that the viability of the deletion mutant indeed depended on the presence of the second-site mutation. Our results corroborate the notion that hydrophobic interactions of protein C are essential for the assembly of infectious flavivirus particles but rule out the possibility that individual residues of the central hydrophobic domain are absolutely required for infectivity. Furthermore, the double mutants were found to be highly attenuated and capable of inducing a protective immune response in mice at even lower inoculation doses than the previously characterized 16-amino-acid-residue deletion mutant, suggesting that the combination of large deletions and second-site mutations may be a superior way to generate safe, attenuated flavivirus vaccine strains.